2014
DOI: 10.1155/2014/675905
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between Gallotannin and a Recombinant Form of Arginine Kinase of Trypanosoma brucei: Thermodynamic and Spectrofluorimetric Evaluation

Abstract: Current chemotherapies against trypanosomiasis are beset with diverse challenges, a situation which underscores the numerous research efforts aimed at finding newer and effective treatments. Arginine kinase of trypanosome has been validated as target for drug development against trypanosomiasis. The present study investigated the interaction between a recombinant form of the arginine kinase (rTbAK) of trypanosome and gallotannin. The interaction between gallotannin and recombinant arginine kinase of Trypanosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Our findings indicate that the apoferritin-nanoparticles (Ag, Au and Pt) or apoferritin interacted with arginine kinase of T. brucei in a way that appreciably decreased the enzyme activity. Apoferritin reduced the activity of the arginine kinase of T. brucei by >90% while the apoferritin-nanoparticles decreased the relative activity of the enzyme by >70%, confirming earlier reports [ 17 , 18 , 19 ]. Due to the small sizes of these particles, both apoferritin and apoferritin-nanoparticles may offer opportunities for the selective inhibition of arginine kinase of T. brucei .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings indicate that the apoferritin-nanoparticles (Ag, Au and Pt) or apoferritin interacted with arginine kinase of T. brucei in a way that appreciably decreased the enzyme activity. Apoferritin reduced the activity of the arginine kinase of T. brucei by >90% while the apoferritin-nanoparticles decreased the relative activity of the enzyme by >70%, confirming earlier reports [ 17 , 18 , 19 ]. Due to the small sizes of these particles, both apoferritin and apoferritin-nanoparticles may offer opportunities for the selective inhibition of arginine kinase of T. brucei .…”
Section: Discussionsupporting
confidence: 90%
“…Several investigations have shown that the arginine kinase of T. brucei could be a target for the development of newer trypanocides [ 9 , 10 , 15 , 16 , 17 , 18 , 19 , 24 , 25 ]. The arginine kinase of T. brucei is an attractive drug target simply because it is not only critical to the survival of bloodstream forms of the parasite particularly under stressful conditions, but the enzyme is completely absent in human hosts [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article titled “Interaction between Gallotannin and a Recombinant Form of Arginine Kinase of Trypanosoma brucei : Thermodynamic and Spectrofluorimetric Evaluation” [ 1 ], there were a typo in Equation (7), where the denominator K2 should be corrected to K1, and an error in Table 2, where the values for Δ H, Δ S, and Δ G were incorrectly calculated. The equation and table are corrected as follows: …”
mentioning
confidence: 99%